A novel biomarker panel for irritable bowel syndrome and the application in the general population - Mujagic, Zlatan; Tigchelaar, Ettje F.; Zhernakova, Alexandra; Ludwig, Thomas; Ramiro-Garcia, Javier; Baranska, Agnieszka; Swertz, Morris A.; Masclee, Ad A. M.; Wijmenga, Cisca; van Schooten, Frederik J.; Smolinska, Agnieszka; Jonkers, Daisy M. A. E. (Scientific reports, 2016)
Biological markers that measure gut health and diagnose functional gastro-intestinal (GI) disorders, such as irritable bowel syndrome (IBS), are lacking. The objective was to identify and validate a biomarker panel associated with the pathophysiology of IBS that discriminates IBS from healthy controls (HC) and correlates with GI symptom severity. In a case-control design, various plasma and fecal markers were measured in a cohort of 196 clinical IBS patients and 160 HC without GI symptoms. A combination of biomarkers, which best discriminates between IBS and HC was identified and validated in an independent internal validation set and by permutation testing. The correlation between the biomarker panel and GI symptom severity was tested in IBS patients and in a general population cohort of 958 subjects. A set of 8 biomarker panel was identified to discriminate IBS from HC with high sensitivity (88.1%) and specificity (86.5%). The results for the IBS subtypes were comparable. Moreover, a moderate correlation was found between the biomarker panel and GI symptom scores in the IBS ( r = 0.59, p < 0.001) and the general population cohorts ( r = 0.51, p = 0.003). A novel multi-domain biomarker panel has been identified and validated, which correlated moderately to GI symptom severity in IBS and general population subjects.